Los factores biopsicosociales a promover por las organizaciones en sus programas de bienestar laboral para incidir en la calidad de vida en el trabajo (2015)
Biopsychosocial factors are the set of programs and benefits that are structured as a solution to the needs of the employee within the organization and is projected into the household and community. The quality of life at work has become an ongoing process of improvement that allows the employee to have a personal, social and career development under favorable conditions of satisfaction, motivation and a positive work performance, achieving an impact on the organization both in terms of productivity and in terms of interpersonal relationships so we conclude this work by improvement programs, communication and permanent integration, teamwork, and activities that enable the development and employee quality of life is connected to improving reviewers.